Liquid crystalline inverted lipid phases encapsulating siRNA enhance lipid nanoparticle mediated transfection - Roy Pattipeiluhu; Ye Zeng; Marco M.R.M. Hendrix; Ilja K. Voets; Alexander Kros; Thomas H. Sharp (Nature Communications, 2024)
Abstract Efficient cytosolic delivery of RNA molecules remains a formidable barrier for RNA therapeutic strategies. Lipid nanoparticles (LNPs) serve as state-of-the-art carriers that can deliver RNA molecules intracellularly, as exemplified by the recent implementation of several vaccines against SARS-CoV-2. Using a bottom-up rational design approach, we assemble LNPs that contain programmable lipid phases encapsulating small interfering RNA (siRNA). A combination of cryogenic transmission electron microscopy, cryogenic electron tomography and small-angle X-ray scattering reveals that we can form inverse hexagonal structures, which are present in a liquid crystalline nature within the LNP core. Comparison with lamellar LNPs reveals that the presence of inverse hexagonal phases enhances the intracellular silencing efficiency over lamellar structures. We then demonstrate that lamellar LNPs exhibit an in situ transition from a lamellar to inverse hexagonal phase upon interaction with anionic membranes, whereas LNPs containing pre-programmed liquid crystalline hexagonal phases bypass this transition for a more efficient one-step delivery mechanism, explaining the increased silencing effect. This rational design of LNPs with defined lipid structures aids in the understanding of the nano-bio interface and adds substantial value for LNP design, optimization and use.